1983
DOI: 10.1016/0042-6822(83)90498-1
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic relationships of murine coronaviruses: Analysis using monoclonal antibodies to JHM (MHV-4) virus

Abstract: Monoclonal antibodies were produced to JHMV-DL, a neurotropic member of the mouse hepatitis virus (MHV) or murine coronavirus group. Of 23 antibodies isolated, 10 were specific for the major envelope glycoprotein, gp180/90, 10 for the nucleocapsid protein, pp60, and 3 for the minor envelope glycoprotein, gp25. Eleven different MHV isolates were used in antibody binding assays to study antigenic relationships among the viruses. Each MHV isolate tested had a unique pattern of antibody binding, indicating that ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
138
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(141 citation statements)
references
References 35 publications
3
138
0
Order By: Relevance
“…A comparative study of nine TGEV strains, using a panel of neutralizing MAbs that recognized four major antigenic sites and at least nine possible epitopes, distinguished two variants by seroneutralization, which could not be distinguished using conventional sera . Nevertheless, distinct antigenic strains as defined for murine coronaviruses and IBV, where each isolate has a unique pattern of reactivity with antiglycoprotein MAbs (Fleming et al, 1983), was not reported for TGEV. Four epitopes were defined on the haemagglutinin of BCV .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative study of nine TGEV strains, using a panel of neutralizing MAbs that recognized four major antigenic sites and at least nine possible epitopes, distinguished two variants by seroneutralization, which could not be distinguished using conventional sera . Nevertheless, distinct antigenic strains as defined for murine coronaviruses and IBV, where each isolate has a unique pattern of reactivity with antiglycoprotein MAbs (Fleming et al, 1983), was not reported for TGEV. Four epitopes were defined on the haemagglutinin of BCV .…”
Section: Discussionmentioning
confidence: 99%
“…The peplomeric E2 glycoprotein is often cleaved post-translationally by host cell proteases into two 85K to 100K subunits (Sturman et al, 1985;Cavanagh et al, 1986b). The latter also is known to be responsible for virus attachment and cell membrane fusion (Collins et al, 1982), and elicits the production of virus-neutralizing antibodies (Fleming et al, 1983;Laude et al, 1986;Niesters et al, 1987; which may be protective (Buchmeier et al, 1984;Wege et al, 1984;Cavanagh et al, 1986a). An additional glycoprotein of 130K to 140K, a disulphide-linked dimer of 65K subunits, is associated with the haemagglutinin (E3) of viruses belonging to the subgroup of haemagglutinating mammalian coronaviruses (King et al, 1985 ;Hogue & Brian, 1986: Sugiyama et al, I986).…”
Section: Introductionmentioning
confidence: 99%
“…revealed no differences in either the number or the distribution of viral antigen in spinal cords of mice treated with either rat IgG (A) (magnification, ϫ100) or anti-NKG2D (B) (magnification, ϫ100). Viral antigen was detected by immunoperoxidase staining by using anti-JHMV MAb J.3.3, and antigen-positive cells were demonstrated by the presence of chromogen (arrows) (28,90). Representative LFB-stained spinal cord sections from JHMV-infected cells at day 32 p.i.…”
Section: Discussionmentioning
confidence: 99%
“…Slides containing stained spinal cord sections were blinded and scored by three investigators, and scores were averaged and are presented as averages Ϯ standard errors of the means (SEM). The distribution of viral antigen was determined by immunoperoxidase staining (Vectastain-ABC kit; Vector Laboratories, Burlingame, CA) using the anti-JHMV MAb J.3.3 specific for the carboxyl terminus of the viral nucleocapsid protein as a primary antibody and horse anti-mouse IgG as the secondary antibody (Vector Laboratories, Burlingame, CA) (7,28,90). The data presented represent a minimum of six spinal cord sections per mouse with no fewer than three mice per time point.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that there are some MHV antigen strains with partially different antigen constructions [1] . Machii et al [5] investigated reactivties of four murine coronavirus antigens (SDAV, PCV, MHV-S and MHV-NuU) with rat antisera and demonstrated cross-reactivity of MHV-S and MHV-NuU antigens with SDAV and PCV antisera.…”
Section: Discussionmentioning
confidence: 99%